PENGARUH PERSEPSI ATAS KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU - Satrio Pamungkas (LPPM Universitas Asa Indonesia, 2015)
Principal leadership is the principal behaviors in influencing teachers to work effectively and efficiently so that the intended purpose can be achieved. in the lead, each principal has a different perception of teachers, there are teachers 'perceptions of authoritarian leadership, laissez faire, demokratis.maka teachers' perceptions on the relationship of leadership will bring in creating a better teacher performance.